Is serum Fibroblast Growth Factor 21 associated with the severity or presence of coronary artery disease? FGF-21 and coronary artery disease - Nar, Gokay; Cetin Sanlialp, Sara; nar, rukiye; Kilic, Oguz; Ozen, Mehmet Furkan; Gunver, Guven; Sevgican, Cihan Ilyas (Journal of Medical Biochemistry, 2021)
Aim: Recent studies have shown that increased circulating concentrations of fibroblast growth factor 21 (FGF21) are associated with obesity, metabolic disorder, and atherosclerosis. However, the studies which investigate the relationship between serum FGF21 levels and coronary artery disease (CAD) include conflicting data. In this study, we planned to investigate the role of FGF21 in CAD development and CAD severity.Method: Seventy-eight patients with stable angina pectoris (SA) (lesion positive) and 40   control patients (lesion negative) with similar cardiovascular risk factors who underwent coronary angiography were included in the study. Serum FGF21 levels were measured by ELISA method. CAD severity was evaluated by using SYNTAX and GENSINI risk scores.Results:  Although there was a statistically significant difference between serum FGF21 levels in the SA and the control groups [101.18 ± 141.62 vs. 47.93 ± 58.74 pg/mL; p = 0.03], no correlation was found between the SYNTAX (r = 0.146 and p = 0.134) and GENSINI (r = 0.211 and p = 0.084) scores with serum FGF21 levels. The SA group had lower serum HDL-C levels (41.57 ± 11.40 vs. 54.90 ± 34.47; p = 0.02). There was a significant and negative relationship between serum FGF21 and serum HDL-C levels in correlation analysis (r = - 0.272; p = 0.026).Conclusion: The serum FGF21 levels are different between SA diagnosed and control patients. FGF21 may be a marker for CAD diagnosis, but not for the evaluation of CAD severity. To the best of our knowledge, this is the first study to evaluate coronary artery disease severity together with a lipid profile.
Keywords: Coronary artery disease; FGF-21; Stable angina pectoris